Study of the principles involved in the activation of indocyanine green by infrared radiation in the photodynamic inactivation of pneumonia - Tovar, Johan Sebastian Diaz (2020)
Pneumonia is one the main causes of death worldwide, and it is mainly due to the increase of antibiotic microbiological resistance. Photodynamic therapy (PDT), which uses the combination of light and a photosensitizer (PS) drug to cause damages in biological target, has emerged as a non-invasive clinical approach for different kind of treatment to which development of resistance is reported to be unlikely. Our research group has demonstrated the efficient of photodynamic inactivation (PDI) of Streptococcus pneumoniae in vitro and in vivo using Indocyanine green as a PS. In this work was investigated the efficient of generation of reactive oxygen species (ROS) of Indocyanine green (ICG) by comparing two wavelengths, 780 and 808 nm. As well as the efficient of 808 nm wavelength to pass through structures with similar optical properties of skin and activate ICG by extracorporeal illumination to generate PDI in Streptococcus pneumoniae. For the first part of the work, photobleaching experiments were performed at 780 and 808 nm, different oxygen concentrations and solvents. Sensitizer bleaching was recorded by absorption spectra and then analysed by using the PDT bleaching macroscopic model to extract important parameters of ICG. It was found higher photobleaching rates when degradating with 808 nm than 780 nm wavelength, and deactivation of ICG molecule was observed to be due to type I and type II mechanisms of PDT. For second part, the PDI efficiency was validated when incident light is attenuated by phantom barriers. Characterization of the panel of 200 laser prototype was performed by emission wavelength, irradiance statibility and temperature increase. The optical transmission attenuated light was detected as phantom barriers increased. On the other hand, Monte Carlo simulation were performed in a computerized model phantom of the thoracic cage to . Finally, for the PDI experiments it was found that even with a barrier thickness of 37.10 mm a energy dose of 197.96 J/cm2 at surface of the laser panel/phantom interface is needed to achieve a total reduction of the bacterial burden. In conclusion, ICG in combination with extracorporeal illumination at 808 nm wavelength demonstrate a high efficient for treatment of lung infections as pneumonia.